An explicit derivation of the time–information uncertainty relation in thermodynamics. (4th March 2021) - Tanabe, Katsuaki
Abstract: A direct, explicit derivation of the recently discovered time–information uncertainty relation in thermodynamics [S. B. Nicholson et al (2020), Nat. Phys. 16, 1211] is presented.